Policy Prediction and Image Search on Content Sharing Sites - George, Neema; Joseph, Neena; James, Merlin Mary; Kurian, Simy Mary (International Journal of Computer Sciences and Engineering, 2019)
Client can share their own data like pictures with different clients through satisfied sharing destinations. Tragically the security of transferred pictures in satisfied sharing site become a significant issue. To conquer this issue CHUI based Privacy Policy Prediction system and NPK for protection strategy based picture search are presented . CHUI ( Closed High Utility Itemsets) based Framework decides the best protection strategy for the transferred pictures and NPK (Non-Parametric Kernel) for picture search in secure way.